2021
DOI: 10.3390/ani11113035
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Equine Reproduction

Abstract: Bacteria develop resistance to antibiotics following low-level “background” exposure to antimicrobial agents as well as from exposure at therapeutic levels during treatment for bacterial infections. In this review, we look specifically at antimicrobial resistance (AMR) in the equine reproductive tract and its possible origin, focusing particularly on antibiotics in semen extenders used in preparing semen doses for artificial insemination. Our review of the literature indicated that AMR in the equine uterus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…There are several reports (reviewed recently [ 3 ]) concerning the AMR of bacteria isolated from uterine swabs, uterine lavage, vaginal swabs and clitoral swabs from the equine reproductive tract, mostly in cases of clinical disease or fertility problems. Briefly, resistance among isolates from the reproductive tract of mares has been reported in several countries including France [ 4 ], Sweden [ 5 ], India [ 6 , 7 ], Italy [ 8 , 9 , 10 ], Germany [ 11 ], the US [ 12 , 13 ], Slovakia [ 14 ] and Turkey [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports (reviewed recently [ 3 ]) concerning the AMR of bacteria isolated from uterine swabs, uterine lavage, vaginal swabs and clitoral swabs from the equine reproductive tract, mostly in cases of clinical disease or fertility problems. Briefly, resistance among isolates from the reproductive tract of mares has been reported in several countries including France [ 4 ], Sweden [ 5 ], India [ 6 , 7 ], Italy [ 8 , 9 , 10 ], Germany [ 11 ], the US [ 12 , 13 ], Slovakia [ 14 ] and Turkey [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO warns about A. baumannii and P. aeruginosa as critical microorganisms in terms of their resistance profile ( Allen et al , 2011 ; OMS, 2017 ), species belonging to the same genera found in this research. It is necessary to deepen the knowledge about these microorganisms in the equine and its clinical environment, to elucidate what is the role that they play in the uterine environment of mares and the potential transmission to humans and their environment ( Malaluang et al , 2021 ). On the other hand, Staphylococcus equorum , Shigella sonnei , Arthrobacter ramosus , and P. amygdali were also species with a high relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa and S. equi subsp. zooepidemicus may be recovered from those sites, often after mating [ 67 , 68 ]; Cerny et al [ 67 ] indicated that a possibility of bacterial transfer to the stallion’s genital tract during mating could not be excluded.…”
Section: Bacteria In the Reproductive System Of Equidsmentioning
confidence: 99%
“…and Klebsiella spp. recovered from mares in which artificial insemination was used showed antibiotic resistance more frequently than similar bacteria obtained from non-inseminated animals [ 68 ].…”
Section: Antibiotic Resistance As a Limiting Factor In Treatmentmentioning
confidence: 99%